Defining ecological reference conditions in naturally stressed environments – How difficult is it?. (April 2020) - Hess, Silvia; Alve, Elisabeth; Andersen, Thorbjørn J.; Joranger, Tore
Abstract: The present study performed in Horten Inner Harbor (southern Norway) shows that foraminifera link the present-day Ecological Quality Status (EcoQS) to EcoQS of former times and, this way, bridge an important knowledge gap concerning determination of reference conditions, even in naturally stressed environments such as transitional waters and oxygen depleted habitats. In Horten Inner Harbor, geochemical data in the oldest deposits showed stable background concentrations for about 200 years (from about 1600 to 1800) before human activity became noteworthy, reflecting 'good' to 'high' status. Hence, it is reasonable that organisms, which lived in the area during the same nearly un-impacted time interval, represent the biologically defined reference conditions, irrespectively of whether the biotic indices are classified as 'good' or 'bad'. The present paper illustrates, with a conceptual model, how the retrospective foraminiferal biomonitoring method can be used to detect environmental perturbations in estuaries and meet the difficulties of the Estuarine Quality Paradox. Highlights: Multiproxy study to reconstruct the pollution history of a harbor basin in S′ Norway. Assessment of in situ ecological reference conditions. Foraminifera link recent to past Ecological Quality Status in stressed environments. Conceptual model illustrating the use of the retrospective foraminiferal bio-monitoring method.